Complementary and Alternative Therapies Used by Patients of Pediatric Dermatology Outpatient Clinics in Turkey: A Multicenter Study. Issue 1 (22nd November 2016) - Can, Burce; Akan, Hülya; Topaloglu Demir, Filiz; Zindanci, Ilkin; Cebeci, Filiz; Turkoglu, Zafer; Kavala, Mukaddes
Abstract: Background: The aim of this study was to determine the frequency of complementary and alternative medicine (CAM) methods used in children and adolescents with chronic skin diseases, which methods parents prefer, and to what extent these methods are useful. Material and methods: This cross‐sectional study was conducted between June and November 2014 in patients with chronic skin diseases attending the outpatient pediatric dermatology clinics of three hospitals in Turkey. Data were collected using self‐administered questionnaires from the parents of the patients. Results: A total of 307 patients were included in the study, 168 (54.7%) of whom were female and 139 (45.3%) male. The mean age was 12.3 ± 4.3 years. Eighty of the children (26.1%) had used CAM methods in the previous year. Longer disease duration and having a father with at least a university degree were highly associated with CAM use (p < 0.05). The most used method was herbal remedies available at home. Most patients used CAM methods to support the primary treatment given by their dermatologists. Only eight CAM users (2.6%) reported any side effects. Thirty‐nine (48.8%) did not mention CAM use to their doctors. The overall satisfaction rate was 4.5 ± 3.1 on a 10‐point rating scale. Conclusion: CAM use rates are high in children with chronic skin problems, and parents generally prefer herbal treatments. Satisfaction with the results of CAM use is moderate. Parents generally do not share CAM use information with their doctors unless they are asked.